Icebreaker - Tanner, Lian (Tanner, Lian. Hidden series, 2015)
"Petrel is an outcast on the ancient ship, an icebreaker, that has been following the same course for 300 years. In that time, the ship's crew has forgotten its original purpose and broken into three warring tribes. Everyone has a tribe except Petrol. Nicknamed the Nothing Girl, Petrel has been ostracized ever since her parents were thrown overboard as punishment for a terrible crime"--Jacket flap.